History of the national licensing examination for the health professions under the Japanese Government-General of Korea (1910-1945) - In-Soon Park (Journal of Educational Evaluation for Health Professions, 2015)
During the reign of Japanese Government-General of Korea (Joseon) from 1910 to 1945, the main health professionals who were educated about modern medicine were categorized into physicians, dentists, pharmacists, midwives, and nurses. They were clearly distinguished from traditional health professionals. The regulations on new health professionals were enacted, and the licensing system was enforced in earnest. There were two kinds of licensing systems: the license without examination through an educational institution and the license with the national examination. The Japanese Government-General of Korea (Joseon) combined education with a national examination system to produce a large number of health professionals rapidly; however, it was insufficient to fulfill the increasing demand for health services. Therefore, the government eased the examination several times and focused on quantitative expansion of the health professions. The proportion of professionals licensed through national examination had increased. This system had produced the maximum number of available professionals at low cost. Furthermore, this system was significant in three respects: first, the establishment of the framework of the national licensing examination still used today for health professionals; second, the protection of people from the poor practices of unqualified practitioners; and third, the standardization of the quality of health.